2021
DOI: 10.1155/2021/6658081
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solutions of Newell-Whitehead-Segel Equations Using Symmetry Transformations

Abstract: In this article, Lie and discrete symmetry transformation groups of linear and nonlinear Newell-Whitehead-Segel (NWS) equations are obtained. By using these symmetry transformation groups, several group invariant solutions of considered NWS equations have been constructed. Furthermore, some more group invariant solutions are generated by using discrete symmetry transformation group. Graphical representations of some obtained solutions are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The applications of Lie symmetry analysis have been used in many research for solving nonlinear partial dierential equations found in physical problems [2,26,4,7,3,6,32,8] and for mathematical Models such as SIR models [33]. But in this project, we put a signicant emphasis on discussing the idea of symmetries of ODEs and demonstrate how their features can be used to obtain the exact solutions.…”
Section: −2ξmentioning
confidence: 99%
“…The applications of Lie symmetry analysis have been used in many research for solving nonlinear partial dierential equations found in physical problems [2,26,4,7,3,6,32,8] and for mathematical Models such as SIR models [33]. But in this project, we put a signicant emphasis on discussing the idea of symmetries of ODEs and demonstrate how their features can be used to obtain the exact solutions.…”
Section: −2ξmentioning
confidence: 99%
“…[1]. Recently, several methods have been used to find exact solutions of nonlinear model equations like Cahn-Allen equation [2], ð2 + 1Þ -dimensional Date-Jimbo-Kashiwara-Miwa (DJKM) equation [3], Newell-Whitehead-Segel (NWS) equations [4], the Chaffee-Infante equation [5], DNA Peyrard-Bishop equation [6], Burger's equation [7], the ð2 + 1Þ-dimensional nonlinear Sharma-Tasso-Olver equation [8], and Ablowitz-Kaup-Newell-Segur water wave equation [9]. Recently, a number of concrete techniques have been recognized for finding accurate and comprehensible solutions of nonlinear physical models with the help of computer algebra, such as Maple, MATLAB, and Mathematica.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of concrete techniques have been recognized for finding accurate and comprehensible solutions of nonlinear physical models with the help of computer algebra, such as Maple, MATLAB, and Mathematica. These include power ondex method [7,9], lie symmetry groups [3,4], new extended direct algebraic method, and the generalized Kudryashov method [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [9] and [10] Khalil and Khadija used the power index method to find new exact solutions of the Ablowitz-Kaup-Newell-Segur water wave equation and Burger's equation. Transformations of variables can sometimes be found that transform a nonlinear PDE into a nonlinear ODE such as Lie Symmetry Transformations [11], [12]. The phenomenon of a soliton with constant shape and speed was proposed by Russell in 1834, which he called a translational wave [8].…”
Section: Introductionmentioning
confidence: 99%